TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENIPUAN DALAM TRAKSAKSI ELEKTRONIK - Indiantoro, Alfalachu; Firdausi, Ulya Shafa; Febriansyah, Ferry Irawan; Qurata, Azhar; Isnandar, Aries (Universitas Muhammadiyah Ponorogo, 2024)
One of the major developments in legal technology is the use of computerized information and case management systems. Fraud in electronic/online transactions is basically the same as fraud in general. Electronic transactions refer to the process of buying and selling, services, goods or information through the internet network media. Here are a few; Inappropriate products, price discounts, free shipping services, special events, fake accounts / fake accounts / falsified identities. Normative Legal Research is a legal research method used to collect data and analyze literature. Normative legal research focuses on positive legal principles with the discipline of studying legal doctrine and analyzing certain legal cases. Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) and Law Number 19 of 2016 concerning Amendments to the ITE Law are relatively new legal regulations. In the context of using the internet, information networks and electronic transactions, it is mandatory to comply with the provisions in the ITE Law Article 3. Fraud in electronic transactions can result in civil and criminal law consequences. In civil law, perpetrators of fraud can be forced to compensate victims. On the other hand, in criminal law, perpetrators of fraud can face criminal penalties in accordance with applicable regulations. It is very important to adhere to principles such as good faith, fairness, etc. when engaging in an electronic transaction. In addition, maintaining the principle of vigilance is very important for sellers when shipping goods and for buyers when sending payments to minimize the risk of fraud.